Certificações nas redes de consumo: profissionais de PDV e o Selo Procel nos produtos - Noronha, Matheus Eurico Soares de (2018)
In a scenario in which political and environmental issues permeate society, several mechanisms are created that contribute to a more conscious and responsible consumption. The certifications appear as a response to the manifestation of the Market, Government and Consumer. With the creation of these certifications to guide the production and consumption spheres, it is understood the need to transmit the information about the functionality of the certifications in a clear and transparent way. Among several certifications currently in the markets, there is the PROCEL-INMETRO certification. What is questioned is the actual knowledge about this certificate. Can the vectors of this information transparently convey to the public what the certificate really means? This dissertation has two main objectives: To identify how point-of-sale professionals are informed about the certificate; check how these professionals transmit information about the certificate at the time of sale. In order to meet the objectives of the study, a qualitative research was carried out with 35 retail store sellers from the regions of Praia Grande, São Paulo and Guarulhos. Sellers presented the different ways they learned about the certificate and relevance when transmitting the information they possessed from the certificate.